2021
DOI: 10.3389/fsurg.2021.672669
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Diagnosis and Treatment of Primary Retroperitoneal Liposarcoma

Abstract: Background: Primary retroperitoneal liposarcoma (PRPLS) is the most common soft tissue sarcoma of the retroperitoneum with high recurrence rate and short overall survival (OS).Methods: A retrospective review of 51 patients with PRPLS, treated between September 1, 2009 and November 30, 2020, was conducted to evaluate clinical outcomes of PRPLS resection. Patient demographics, histopathologic subtypes, overall survival (OS), progression-free survival (PFS), disease recurrence rate, and tumor stage were reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Concomitant organ resection was not associated with better DFS (HR 1.022, 95% CI 0.537 to 1.946, P value 0.946). Retrospective hospital studies of Asian populations reached similar conclusions (39,40) and (Table 4). Table 4 outlines the studies investigating contiguous organ resection in retroperitoneal liposarcomas.…”
Section: Table 3 Outlines the Studies Investigating Contiguous Organ ...supporting
confidence: 61%
“…Concomitant organ resection was not associated with better DFS (HR 1.022, 95% CI 0.537 to 1.946, P value 0.946). Retrospective hospital studies of Asian populations reached similar conclusions (39,40) and (Table 4). Table 4 outlines the studies investigating contiguous organ resection in retroperitoneal liposarcomas.…”
Section: Table 3 Outlines the Studies Investigating Contiguous Organ ...supporting
confidence: 61%
“…While rare, retroperitoneal liposarcomas (LPS) are locally aggressive tumors that present significant clinical challenges and are associated with a dismal prognosis [ 1 , 2 ]. Surgical resection remains the only chance for long-term survival [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Singer et al [ 34 ] have demonstrated that tumor histology type, tumor grade and contiguous organ resection were significantly associated with tumor recurrence, while tumor size was not an independent risk factor. A retrospective study by Chen et al [ 36 ], including 51 patients with primary RPL, showed that tumor size was not an independent risk factor for recurrence or prognosis on univariate and multivariate analysis. The findings of the previous studies including our review exclude tumor size as a prognostic factor for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%